Phänomenologie des Pop - Mühleis, Volkmar (Verlag Karl Alber, 2026)
The alien is fundamental to the experience of international pop culture. However, it is hardly reflected in pop theory. At the same time theory makes use of numerous phenomenological figures of thought - such as lifeworld or response - without exploring them. Together, this creates a gap that only a phenomenology of pop can close. The ‘Phenomenology of Pop’ offers an initial approach to this. The book combines the current discourse in both academic and free pop theory with the current state of research in phenomenology, to provide food for thought in both directions. It concludes with an inventory of the concept of pop, embedded in examples from the ABBA arena in London to Chinese punk.